THE IMPORTANCE OF THE ROLE OF LOCAL FOOD IN GEORGIAN TOURISM - Meladze, Maia (European Scientific Journal, ESJ, 2016)
The top three activities undertaken in Georgia by international travelers are: rest and relaxation (36%), tasting Georgian dishes (35%), exploring Georgian nature/landscape (35%), etc. Gastronomy has become one of the most important parts of a tourism market. Georgia is a unique country – as a homeland of wine and a country which is distinctive for its plenty of ethnographic regions. Each historical-ethnographic region had its own natural and agricultural specificity, which led to the peculiarity of the ethnic group feeding. A great Majority of foreign tourists, who tries Georgian traditional dish for the first time, declares about its best taste and scent at once. Georgia’s traditional winemaking method of fermenting grapes in earthenware, egg-shaped vessels has been added to the world heritage list of the UNESCO. Georgian gastronomic diversity is a great resource for tourism development in the country. Friendliness and goodwill of a tourist greatly depends on the dishes and beverages they are offered.